ANALISIS PROSES “DRY AGING” TERHADAP TINGKAT KESUKAAN KONSUMEN KEPADA PRODUK DAGING SAPI DI PT. ANGGANA CATUR PRIMA - Saleha; Rima Pratiwi Batubara; Muhammad Azmi Fakhrusy (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2022)
The “Dry aging” process to improve the taste and tenderness of meat is used very little by meat providers, high-end hotels and restaurants for sale to the general public. “Dry aging” is the process by which carcasses or large pieces of beef are stored without protective packaging at refrigeration temperature for one to five weeks to allow for “enzymatic” and “Biochemical” processes that increase tenderness and the appearance of a unique aroma that can only be described as “dry aged” beef. This study uses a quantitative approach method. Data analysis with descriptive statistical analysis. The samples studied were 40 untrained panelists and 4 expert panelists who were beef consumers at PT. Anggana Catur Prima and an expert in the culinary field. This research was conducted to determine whether or not the